Macro-Mesoscale Submodeling Approach for Analysis of Large Masonry Structures - S. Pietruszczak; P. Przecherski (Buildings, 2025)
In this work, a sub-modeling technique is proposed for the analysis of large-scale masonry structures. The approach couples an anisotropic macroscale formulation, derived by incorporating the notion of a fabric tensor for an orthotropic material, with mesoscale analysis. The latter employs distinct inelastic constitutive relations assigned to the brick material and brick-mortar interfaces, which enable the tracing of localized damage propagation. The mechanical properties at the macro-level are identified from the ‘virtual’ set of data generated through mesoscale analysis, ensuring consistency between the two approaches in representing the masonry material across different scales. In the numerical analysis, the macroscale approach is first applied over the entire domain to interpolate the kinematic boundary conditions in a local region of interest, which is then re-analyzed based on the mesoscale framework. The developed strategy is illustrated by simulating the shear response of a large-scale unreinforced masonry wall with multiple window openings.